Nonna's birthday surprise - Bastianich, Lidia (RP Kids, 2013)
It's Nonna Mima's birthday, and Nonna Lidia and her grandkids are determined to throw her a surprise feast! While planning the evening's menu, Nonna Lidia shares her memories of growing up on the farm during each season of the year, gardening her own fruits and vegetables, and being surrounded by animals of all kinds. After a trip to the farmers' market, Lidia and the kids prepare a pasta primavera, perfect for a family celebration!--Publisher's description.